Multifocal Leukoencephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A 15-year-old boy with Wiskott-Aldrich syndrome complicated by progressive multifocal leukoencephalopathy (PML) is reported from the University of Miami School of Medicine, FL, and the National Institute of Neurological Disorders and Stroke, Bethesda, MD.